Water-borne cues induce chemical defense in a marine alga (Ascophyllum nodosum) - Toth, Gunilla B. (The National Academy of Sciences, 2000)
It is well known that herbivores can induce chemical defenses in terrestrial vascular plants, but few examples of inducible production of defense chemicals have been reported for aquatic macrophytes. Furthermore, it is well established that water-borne chemical cues from predators or predator-wounded conspecifics can induce defensive changes of aquatic prey animals, but no such communication between aquatic herbivores and seaweeds has been reported. Here we show that water-borne cues from actively feeding herbivorous gastropods, flat periwinkles (Littorina obtusata), can serve as external signals to induce production of defense chemicals (phlorotannins) in unharmed individuals of seaweeds, knotted wrack (Ascophyllum nodosum), and that the increased levels of defense chemicals deter further feeding by periwinkles. Because seaweeds have poorly developed internal-transport systems and may not be able to elicit systemic-induced chemical defenses through conveyance of internal signals, this mechanism ensures that seaweeds can anticipate future periwinkle attacks without receiving direct damage by herbivores.